b - 9 (b, 1995)
Survey on reports of the task forces on Bangladesh development strategies for 1990s.
In Bengali.
Includes bibliographical references (p. 117-120).
Keywords: Economic development projects -- Bangladesh; Bangladesh -- Economic policy